Selective up-regulation of phosphatidylinositol 3′-kinase activity in Th2 cells inhibits caspase-8 cleavage at the death-inducing complex: a mechanism for Th2 resistance from fas-mediated apoptosis - Varadhachary, Arun S.; Peter, Marcus E.; Krammer, Peter H. (The journal of immunology, 1999)
In this study the mechanism of differential sensitivity of CD3-activated Th1- and Th2-type cells to Fas-mediated apoptosis was explored. We show that the Fas-associated death domain protein (FADD)/caspase-8 pathway is differentially regulated by CD3 activation in the two subsets. The apoptosis resistance of activated Th2-type cells is due to an incomplete processing of caspase-8 at the death-inducing signaling complex (DISC) whereas recruitment of caspase-8 to the DISC of Th1- and Th2-like cells is comparable. Activation of phosphatidylinositol 3′-kinase upon ligation of CD3 in Th2-type cells blocked caspase-8 cleavage to its active fragments at the DISC, thereby preventing induction of apoptosis. This study offers a new pathway for phosphatidylinositol 3′-kinase in mediating protection from Fas-induced apoptosis.
Gesehen am 26.04.2021